SEGMENTASI CITRA BERDASARKAN TEKSTUR MENGGUNAKAN PENGUKURAN LACUNARITY DENGAN METODE DIFFERENTIAL BOX-COUNTING - Dewa Ayu Putu Kania Mulia Utami (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This study aims to design and develop an application that can be used to segment theimage based on texture information using Lacunarity measurements. The method used incalculating Lacunarity is Differential-Box Counting (DBC) method which was firstintroduced by Dong (2000).Implementation of Lacunarity-DBC method on this application produces an applicationcalled "Lacunarity MAP" developed by using programming language Borland Delphi 7. Thisapplication is only able to process RGB and Grayscale images with Bitmap format (*. BMP),and produces output in the form of grayscale images. On the application of "LacunarityMAP" there are three main processes, among others : Lacunarity value calculation in any sizewindow, segmentation of Lacunarity values and edge detection. Testing is done by trying outvarious kinds of images by entering a few parameters such as : box, window, and region.These parameters which will affect the final outcome segmentation of the images. Based onthe results obtained that software testing "Lacunarity MAP" is able to provide maximumresults on several images to include the size of the box : 3,5,11 and 13, while the windowsize: 6, 8, 10, 16, 20 and 22.